Turismo de naturaleza y actividades turísticas en el cantón Guano, provincia de Chimborazo. - Cuvi Cacoango, Bélgica Estefania (2024)
This study investigates nature tourism in Guano, Ecuador, conceptualizing it as a recreational activity that promotes conservation and sustainable development; despite its biodiversity and cultural heritage, Guano faces challenges such as a lack of infrastructure and adequate promotion. The main objective is to analyze the relationship between nature tourism and tourism activities, focusing on environmental sustainability, economic and social impact, tourism management, and the role of service providers, and to improve these areas that would benefit local communities by generating employment and income, thus promoting more sustainable tourism. The methodology used is non-experimental, cross-sectional, and mixed, using qualitative and quantitative methods, with documentary and field data collection. Surveys with a Likert scale were applied to 30 service providers and 15 key actors, processed with SPSS and Excel, ensuring validity with experts from the Universidad Nacional de Chimborazo. The results show a moderate positive correlation between nature tourism and tourism activities (Pearson's coefficient of 0.518, p < 0.01), suggesting that implementing sustainable practices and adequate tourism management contribute to increasing tourism activities in the region. It is concluded that more effective management and promotion of sustainable practices and support for service providers are essential to enhance tourism growth in Guano. In addition, sustainability policies, virtual tourist guides, training for managers and service providers, and facilitating access to resources to improve the local tourism offer are recommended.